Classifying fashion, fashioning class : making sense of women's practices, perceptions and tastes - Appleford, Katherine, 1981- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Drawing together theoretical ideas from across the social sciences, Classifying Fashion, Fashioning Class examines how the fashion-class association has developed and using the experiences of middle-and-working class British women to demonstrates how this relationship operates today. Though increasingly academics argue that contemporary class distinctions are made through cultural practices and tastes, few have fully explored just how individual's fashion choices mobilise class and are used in class evaluations. Yet, individual's everyday dress is perhaps the most immediate marker of taste, and thus an important means of class distinction, and this is particularly true for women, as their performances of respectability, femininity, and motherhood are embodied by fashion and shaped by class. In unpacking this fashion-class relationship, the book explores how fashion is used by British women to talk about class. It offers important insights into the ways fashion mobilises class differences in understandings of dressing up, performance and public space. It considers how class identity shapes women's attitudes concerning fashion trends and classic styles, and it draws attention to the pivotal role mothers play in cultivating these class distinctions. The book will be of interest to students in sociology, fashion studies, cultural studies, human geography and consumer behaviour"--
Introduction : classifying fashion, fashioning class -- Women talking dirty : making sense of fashion & class -- Class fashion or consumer fashion : the relevance of class in contemporary fashion consumption -- Fashioning a performance : respectability, femininity & space -- Dressing up : performance, perceptions & practice -- Looking good : fashion, (dis)taste & buying practices -- Mothers & motherhood : nurturing the fashion-class relationship -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Clothing and dress -- Social aspects -- Great Britain; Fashion -- Social aspects -- Great Britain; Women's clothing -- Social aspects -- Great Britain; Women -- Great Britain -- Attitudes; Social classes -- Great Britain; SOCIAL SCIENCE / Sociology / General